2022
DOI: 10.1136/bmjopen-2021-054741
|View full text |Cite
|
Sign up to set email alerts
|

Biological and clinical correlates of the patient health questionnaire-9: exploratory cross-sectional analyses of the baseline health study

Abstract: ObjectivesWe assessed the relationship between the Patient Health Questionnaire-9 (PHQ-9) at intake and other measurements intended to assess biological factors, markers of disease and health status.Design, setting and participantsWe performed a cross-sectional analysis of 2365 participants from the Baseline Health Study, a prospective cohort of adults selected to represent major demographic groups in the USA. Participants underwent deep phenotyping on demographic, clinical, laboratory, functional and imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…All study procedures and study data collection are conducted in accordance with the principles described in the Declaration of Helsinki and with relevant local, state, national, and international standards. Detailed descriptions of study procedures and methods, including exclusion and inclusion criteria and institutional review board approval and enrollment procedures, have been published [83,84].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All study procedures and study data collection are conducted in accordance with the principles described in the Declaration of Helsinki and with relevant local, state, national, and international standards. Detailed descriptions of study procedures and methods, including exclusion and inclusion criteria and institutional review board approval and enrollment procedures, have been published [83,84].…”
Section: Methodsmentioning
confidence: 99%
“…The Project Baseline Health Study (PBHS) is a prospective cohort study of U.S. adults that has collected a wide array of personal, behavioral, and clinical characteristics that together comprise data sufficiently rich to allow deep phenotyping of study participants [83,84]. In this analysis, we examined participants in the BHS study cohort to identify the most salient factors associated with HGS by examining demographic, socioeconomic status-related health behaviors, medical conditions, symptoms, patient-reported outcomes, and laboratory measures across a wide adult age group while stratifying by age and sex to account for expected differences between these groups.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of questionnaires for self-assessment of the quality of the state of health was justified. It was found that higher PHQ-9 scores were associated with female gender, young age, high body mass index, chronic diseases, higher incidence of comorbidities, and acute diseases (leg cramps, mood changes, lack of energy (p <0:0001) [58].…”
Section: The Level Of Depression As a Reflection Of The State Ofmentioning
confidence: 99%
“…A full description of study procedures and design, inclusion and exclusion criteria, and institutional review board approval has been previously made available. 17,18 This study used cross-sectional data from the first in-person study collection time point; selfreported data used were collected at either the same in-person timepoint or via remote application. We limited data that were only collected remotely to participant responses within 200 days of participants' initial in-person data collection.…”
Section: Project Baseline Health Studymentioning
confidence: 99%
“…Any desire to estimate related causal effects will require an alternative methodological approach. [46][47][48] Second, while the PBHS participants are overall representative of U.S. adult age, sex, race, and ethnicity 18 and were recruited and enrolled at multiple sites, these sites were limited to two states (California and North Carolina) which may limit our ability to generalize these results to adults in other regions of the U.S.. In this study, we identified several novel salient factors with the SLBT, SRT, and 30CST when stratifying by age (<65 and ≥65 years) -many of them common across the three tests.…”
Section: Commonalities Across Biomarkersmentioning
confidence: 99%